Investigation of water splitting using III‐N structures. Issue 8 (17th July 2017) - Usikov, Alexander; Ermakov, Ivan; Helava, Heikki; Kurin, Sergey; Nikiforov, Alexey; Papchenko, Boris; Puzyk, Mike; Polyakov, Alexander; Lee, In‐Hwan; Makarov, Yuri
Abstract : Specifics of the water photoelectrolysis in KOH‐base aqueous solution using GaN‐based structures as working electrodes are studied. The structures were grown by HVPE and MOCVD techniques on sapphire substrates. In highly Si‐doped HVPE‐grown GaN layers ( N D − N A  ∼ 3 × 10 18  cm −3 ) a barrier at the E1 offset potential dominates the current–potential ( I – E ) characteristics. The same dominant E1 offset potential was observed in MOCVD‐grown GaN/InGaN nanopillar structures after the treatment. The Debye screening effect in high‐concentration of KOH electrolyte (20–40 wt.%) that reduces the potential barrier was observed clearly in the defectless nanopillar structures. The corrosion process is initiated in the top p‐type layers via channels associated with threading defects and can penetrate deeply into the structure. It further proceeds in a lateral direction in n‐type layers forming voids and cavities in the structure. The H2 production rate of 0.3–0.6 ml cm −2  h −1 was measured for n‐GaN‐based structure in KOH electrolyte under the Xe‐lamp illumination (concentration factor ×15).